Representation of non-homogeneous material properties using fourier series [electronic resource] - Lee, Fook Ming, 1990- author; Airil Yasreen Mohd. Yassin, supervisor; Fakulti Kejuruteraan Awam (2014)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2014